The smart box: can help students with intellectual disabilities at elementary school inclusive? - Cahyaningtyas, Tiara Intan; Maruti, Endang Sri; Rulviana, Vivi; Rahmawati, Rizka (Universitas Ahmad Dahlan, 2023)
The research addresses the limited availability of learning media supporting education for children with special needs, particularly intellectually disabled students. The study aimed to develop Smart Box media and evaluate its effectiveness in enhancing the learning of Indonesian and Science subjects for these children. Following the ADDIE model, the research employed a research and development (R&D) approach. Data collection included observation sheets, interview sheets, expert evaluations, and student questionnaire surveys. Media expert validation resulted in 83% validity, categorized as very valid, while content expert validation yielded 79%, categorized as valid. Student responses to the trial questionnaire indicated an 88% feasibility rating. The media's effectiveness in supporting learning was evidenced by pretest and posttest scores, which increased from an average of 58 to 86 after its use. In conclusion, the Smart Box media is deemed feasible, engaging, and effective for intellectually disabled students. This research contributes to the advancement of learning media for special needs education, providing a valuable resource for educators and stakeholders in enhancing the learning experience for these students.